Cross section measurement of t-channel single top quark production in pp collisions at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (PHYSICS LETTERS B, 2017)
The cross section for the production of single top quarks in the t channel is measured in proton–proton collisions at 13 with the CMS detector at the LHC. The analyzed data correspond to an integrated luminosity of 2.2. The event selection requires one muon and two jets where one of the jets is identified as originating from a bottom quark. Several kinematic variables are then combined into a multivariate discriminator to distinguish signal from background events. A fit to the distribution of the discriminating variable yields a total cross section of and a ratio of top quark and top antiquark production of . From the total cross section the absolute value of the CKM matrix element is calculated to be . All results are in agreement with the standard model predictions.